Consumption of some Food Groups is Associated with the Risk of Cardiovascular Disease among Jordanians : Food Groups Consumption Cardiovascular Disease - Tayyem, Reema; Azab, Mohammed; Al-Shudifat, Abdel-Ellah; Bawadi, Hiba (Progress in Nutrition, 2020)
Strong evidence suggests the effects certain food groups have reducing or increasing the risk factors for cardiovascular diseases (CVD). However, findings seem to be inconsistent across different populations and even scare in Middle Eastern setting where cardiovascular diseases are endemic. This study aimed at investigating the associations between food groups and risk of cardiovascular disease among Jordanians. A case control study was conducted using convenient sampling method with a total of 400 participants who underwent coronary angiography. Diagnosis of CVD was confirmed by coronary angiography. Case and controls were matched by age and gender with 1:1 ratio. Standardized and validated questionnaires were used to collect socio-demographic, health, lifestyle, and dietary data. Mean age of participants was 56.2+0.55 and 57.2+0.82 for males and females respectively. Food groups with significant influence on prevention or increasing risks for CVD identified in this study are fruits (p=0.024) and Vegetables (p=0.025) but contrary to previous findings, this study identified lower consumption of sweets and sugar among cases of CVD (p=0.007). A U-shape relationship was identified between risk of CVD and consumption of vegetable oil, nuts and seeds (p>0.05). Increased consumption of fruits, vegetables and moderate consumption of vegetables oil and seeds and nuts are may be associated with decreased risk of CVD among Jordanian population.